LIFE CYCLE COST ANALYSIS (LCCA) PROJECT KPBU-AVAILABILITY PAYMENT ON EAST SUMATERA TRAFFIC ROAD PRESERVATION ACTIVITES IN SOUTH SUMATRA PROVINCE - Ardana Yunanda, Erick
Adequate and sustainable road infrastructure is needed to support the implementation of national development to improve the national economy, prosper the community, and increase Indonesia's competitiveness with other countries. To accelerate development and improve road infrastructure services, infrastructure financing innovations through PPP schemes are needed. In this research, an analysis was carried out on the Preservation Activities of the East Sumatra Cross Road in South Sumatra Province, which is the first PPP project in the non-toll road sector. The established method of return on investment is to use an Availability Payment (AP). Life cycle costs are an important consideration in deciding which initial road design to choose. The analysis is carried out by comparing two alternative road designs, namely rigid pavement, and flexible pavement. Life cycle costs consider the overall cost during the pavement life cycle, namely the initial design during the construction period and the road maintenance strategy during the service life. The selection of road management strategies for this project has an effective and efficient life cycle cost value using a rigid pavement design. Types of handling road maintenance to fulfill road performance indicators that have been determined during the service period are routine maintenance of roads and bridges every year and periodic maintenance of functional major rehabilitation in the 10th year of service. The major functional rehabilitation activities are coating work using a layer of asphalt concrete with a thickness of 100 mm. Maximum Availability Payment (AP) value by the government for 12 years on this Project is 200.9 billion per year with an Internal Rate Return value of 11.15% and a Net Benefit Cost Ratio value. of 1.30. The delay in fulfilling the Road Performance Indicators by the Implementing Business Entity will affect the benefits that will be obtained. The choice of the length of the concession period is based on the budget owned by the government, if the budget is large enough, it is better to choose the fastest concession period, but if you have a limited budget or funds, it is better for the government to choose a concession period of 20 years.